ACTIVE GEOTHERMAL SYSTEMS IN THE CONTINENTAL RIFT ZONES OF THE MENDERES MASSIF, WESTERN ANATOLIA, TURKEY - Özgür, N.; Arife Çalışkan, T. (Bulletin of the Geological Society of Greece, 2016)
The active geothermal waters of Kızıldere, Bayındır, and Salihli in the continental rift zones of the Büyük Menderes, Küçük Menderes and Gediz represent typical examples in the study area. The meteoric waters in the drainage areas of the rift zones percolate at NE-SW and/or NW-SE trending fault zones and permeable clastic sediments into the reaction zone of the roof area of a magma chamber situated in a probable depth of up to 5 km where meteoric fluids are heated by the cooling magmatic melt and ascend to the surface due to their lower density caused by convection cells. The volatile components of CO2, SO2, HCl, H2S, HB, HF, and He out of the magma reach the geothermal water reservoir where an equilibrium between altered rocks, gas components, and fluids performs. Thus, the geothermal waters ascend in the tectonical zones of weakness at the continental rift zones of the Menderes Massif in terms of hot springs, gases, and steams. These fluids are characterized by high to medium CO2, H2S and NaCl contents.